Chimeric Antigen Receptor Based Cellular Therapy for Treatment Of T-Cell Malignancies - Polgárová, Kamila; Otáhal, Pavel; Šálek, Cyril; Pytlík, Robert (Frontiers in Oncology, 2022)
T-cell malignancies can be divided into precursor (T-acute lymphoblastic leukemia/lymphoblastic lymphoma, T-ALL/LBL) and mature T-cell neoplasms, which comprise 28 different entities. Most of these malignancies are aggressive with rather poor prognosis. Especially, prognosis of relapsed/refractory (R/R) disease is dismal, with expected survival only several months for progressing patients. Targeted therapies, as are antiCD30 immunotoxin brentuximab vedotin, antiCD38 antibody daratumumab, and anti-CCR4 antibody mogamulizumab, are effective only in subsets of patients with T-cell neoplasms. T-cells equipped with chimeric antigen receptor (CAR-Ts) are routinely used for treatment of R/R B-cell malignancies, however, there are specific obstacles for their use in T-cell leukemias and lymphomas. These are fratricide killing, risk of transfection of malignant cells, and T-cell aplasia. Solution of these problems rely on target antigen selection, CRISPR/Cas9 or TALEN gene editing, posttranslational regulation of CAR-T surface antigen expression, and safety switches. Structural chromosomal changes and global changes in gene expression were observed with gene-edited products. We identified 49 studies of CAR-based therapies registered on www.clinicaltrials.gov. Most of them target CD30 or CD7 antigen. Results are available only for minority of these studies. In general, clinical responses are above 50%, but reported follow-up is very short. Specific toxicities of CAR-based therapies, namely cytokine release syndrome (CRS) seem to be connected with the antigen of interest and source of cells for manufacturing. CRS is more frequent in antiCD7 CAR-T cells than in antiCD30 cells, but it is mild in most patients. More severe CRS was observed after gene-edited allogeneic CAR-T cells. Immune effector cell associated neurotoxicity (ICANS) was mild and infrequent. Graft-versus-host disease (GvHD) after allogeneic CAR-T cells from previous hematopoietic stem cell donor was also observed. Most frequent toxicities, similarly to antiCD19 CAR-T cells, are cytopenias. CAR-based cellular therapy seems feasible and effective for T-cell malignancies, however, the optimal design of CAR-based products is still unknown and long-term follow-up is needed for evaluation of their true potential.